Partitioning beta diversity to untangle mechanisms underlying the assembly of bird communities in Mediterranean olive groves - García-Navas, Vicente; Martínez-Núñez, Carlos; Tarifa, Rubén; Molina-Pardo, José L.; Valera, Francisco; Salido, Teresa; Camacho, Francisco M.; Rey, Pedro J. (Diversity & distributions, 2022)
Aim We investigated taxonomic and functional beta diversity of bird communities inhabiting Mediterranean olive groves subject to either intensive or low‐intensity management of the ground cover and located in landscapes with different degrees of complexity. Location Andalusia, southern Spain. Methods We partitioned taxonomic and functional beta diversity into its two additive components, turnover and nestedness. We also explored the contributions of single sites to overall beta diversity (LCBD) and separated the effects of species replacement (turnover) and richness difference (nestedness) in order to identify ecologically unique sites—keystone communities—within the metacommunity. In a further step, we employed abundance‐ and functional‐based indicator species analyses to characterize bird assemblages. Results Taxonomic beta diversity increased with landscape complexity. Although both taxonomic and functional differences among assemblages were driven mainly by species replacement (regardless of management or landscape type), the contribution of trait replacement to the total functional beta diversity was much lower, suggesting that species performing similar functions replace each other between sites. There were no differences in LCBD between management types or categories of landscape complexity, but the contributions of sites to beta diversity decreased as the percentage cover of olive groves increased. Species richness was also important in explaining variation in LCBD as species‐poor sites tended to contribute the most to the local‐to‐regional beta diversity. However, some farms displayed high values of LCBD due to the existence of a high replacement component, indicating that some species recorded in these sites were scarce elsewhere. The indicator species analyses revealed that the woodchat shrike Lanius senator may constitute an excellent indicator of biodiversity in this agro‐forestry system. Main conclusions Our results show that agricultural expansion promotes biotic homogenization and exemplify how the identification of both keystone species and communities can represent a powerful tool for the management of anthropized landscapes.